Метод количественной оценки профессиональных рисков на предприятиях химико- фармацевтической отрасли - Чикина, Наталья Александровна; Антонова, Ирина Владимировна (НТУ "ХПИ", 2012)
В работе описывается метод количественной оценки профессиональных рисков у рабочих предприятий химико-фармацевтической отрасли на основе анализа кривых резистентности гомеостаза. Метод может быть использован при решении задачи выявления факторов риска заболеваний любой этиологии. Ил.: 3. Библиогр.: 8 назв.

The method of quantitative estimation of professional risks for the workers of enterprises of chemical and pharmaceutical industry is offered. It’s based on analysis of curves of resistibility of homoeostasis. The method can be used for the decision of task of detection of risk factors of diseases of any etiology. Figs.: 3. Refs.: 8 titles.
Method of quantitative estimation of professional risks on the enterprises of chemical and pharmaceutical industry
Keywords: химико-фармацевтическая промышленность; аллергические заболевания; резистентность гомеостаза; факторы риска; профессионально обусловленные заболевания; quantitative estimation; professional risks; resistance homeostasis; risk factors